2016
DOI: 10.1111/sltb.12315
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal–Psychological Theory, Alexithymia, and Personality Predict Suicide Ideation among Maladjusted Soldiers in Taiwan

Abstract: This case-control study enrolled 226 maladjusted soldiers and 229 controls to investigate the impact of the interpersonal-psychological theory of suicide, alexithymia, personality, and childhood trauma on suicide risk among Taiwanese soldiers. Assessments included the Toronto Alexithymia Scale, Eysenck Personality Inventory, Mini-International Neuropsychiatric Interview, and Brief Symptom Rating Scale. In addition to thwarted belongingness and perceived burdensomeness, other risks included less extraversion wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…(1988)USACross-sectional125Substance dependent in-patients40.8 (11.2)125 (100%)TAS-26History taking – lifetime attemptHintikka et al. (2004)FinlandLongitudinal1563General population45.1 (10.5)649 (42%)TAS-20BDI item 9Huang et al. (2016)TaiwanCase-control455Maladjusted soldiers, controls21.9 (4.5)429 (95%)TAS-20BSRSIancu et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1988)USACross-sectional125Substance dependent in-patients40.8 (11.2)125 (100%)TAS-26History taking – lifetime attemptHintikka et al. (2004)FinlandLongitudinal1563General population45.1 (10.5)649 (42%)TAS-20BDI item 9Huang et al. (2016)TaiwanCase-control455Maladjusted soldiers, controls21.9 (4.5)429 (95%)TAS-20BSRSIancu et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2012)TAS-20Standardised B = 0.54*Standardised B = 0.21*Non-significant – no values given†DepressionDe Berardis (2008)TAS-20pr=0.72⁎⁎⁎pr=0.64⁎⁎⁎pr=0.20†Demographic variablesDe Berardis (2013)TAS-20Standardised B = 0.31⁎⁎Non-significant – no values given†Non-significant – no values given†Demographic variables, panic disorder, depression, laboratory variables, TAS-20 subscalesDe Berardis (2014)TAS-20Standardised B = 0.54*Non-significant – no values given†Non-significant – no values given†Demographic variables, OCD, depression, laboratory variables, TAS-20 subscalesDe Berardis (2015)TAS-20Standardised B = 0.29⁎⁎⁎Non-significant – no values given†Non-significant – no values given†Demographic variables, OCD, depression, responsibility attitudes, TAS-20 subscalesDe Berardis (2017)TAS-20pr=0.70⁎⁎⁎pr=0.53⁎⁎⁎pr=0.58⁎⁎⁎Demographic variablesGhorbani et al. (2017)TAS-20 r = 0.42⁎⁎⁎pr=0.12† r = 0.53⁎⁎⁎pr=0.29⁎⁎⁎ r = 0.58⁎⁎⁎pr=0.42⁎⁎⁎Depression, alcohol dependence severityHuang et al. (2016)TAS-20 d = 1.03*Standardised B = 0.03⁎⁎ d = 1.64…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a German population‐based study found that people with high N increased the risk of suicide (SI or SA) to 1.64‐fold . Among maladjusted soldiers in Taiwan, higher N is linked with more maladjustment ( P < 0.01) and increased the risk for SI ( P < 0.05) . Moreover, trait N was suggested to be a useful marker to predict future SA in a longitudinal study based on a birth‐cohort following 21 years .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these results were contrary to a well-established link between ideation and attempts and FFM personality. In particular, suicide ideation is most associated with low extraversion (Deshong et al, 2015;Huang et al, 2017;Chioqueta and Stiles, 2005), high neuroticism (Rappaport, Flint, and Kendler, 2017;Tucker et al, 2016;Chioqueta and Stiles, 2005), high openness to new experiences (Chioqueta and Stiles, 2005), low agreeableness (Kerby, 2003) and low conscientiousness (Kerby, 2003;Velting, 2003). Similarly, high neuroticism and low extraversion seem to be the most related to suicide attempts and completed suicides (Brezo et al, 2006;Duberstein et al, 2005;Kiekens et al, 2015).…”
Section: Discussionmentioning
confidence: 99%